Study on the whole-grain magnetic–float combination beneficiation process of high mud lithium mica - Rongrui WANG; Yongbiao CHENG; Junhao FU; Haisheng HAN; Jie DING; Jianhua KANG; Yong LI (工程科学学报)
The South China region is abundant in high mud lithium mica resources, which are characterized by their complex mineral composition and high fine mud content. These properties present significant challenges for flotation separation, resulting in low resource utilization rates. Geochemical studies have identified an evolutionary trend of lithium mica: Biotite evolving into Ferrimuscovite, then Zinnwaldite, Trilithionite, and finally Lithium mica. During this evolution, some lithium mica acquires weak magnetic properties owing to iron content, making it suitable for superconducting magnetic separation technology. This technology offers high magnetic field strength and low particle size limitations, offering great application prospects. This paper addresses the high mud lithium mica resource at Jiepailing, Hunan Province. The main lithium-bearing minerals in this ore are iron-bearing lithium mica, constituting 21.43% of the ore. Owing to the fine size of these target minerals, fine grinding is essential to increase monomer dissociation before beneficiation. The ore contains kaolinite and other vein minerals, which are easy to be muddied after grinding, making the amount of fine mud greatly increase. Additionally, the ore contains high amounts of fluorite, which negatively affects the flotation process for lithium mica concentration. The presence of high fluorite and fine mud content limits the efficacy of conventional flotation methods. Furthermore, the weak magnetic properties of certain lithium mica minerals pose challenges for conventional high-gradient magnetic separation techniques. Therefore, a new combined magnetic–flotation sorting process has been developed based on the ore characteristics. Stronger magnetic zinnwaldite is preferentially separated and enriched through high-gradient magnetic separation. Subsequent secondary grinding allows for another round of magnetic separation to obtain high-grade concentrate. Weakly magnetic lithium mica is pre-enriched by flotation, reducing throughput after impurity removal. Finally, the flotation concentrate and fine sludge are separated and enriched using superconducting technology. This process finally causes “high-gradient magnetic separation—fluorite removal flotation—lithium mica flotation—superconducting magnetic separation” of the whole particle size beneficiation. Experimental results have shown that microfine-grained lithium mica, which cannot be effectively separated by conventional magnetic separation or flotation methods, can a Li2O grade increase from 0.52% to 1.86% using superconducting magnetic separation technology. This greatly improves the ore utilization rate. Under full process experimentation, raw ore with a 0.76% Li2O grade yielded a comprehensive lithium mica concentrate with a 2.22% Li2O grade and a 77.62% recovery rate. The new process bypasses the shortcomings of conventional separation methods through the organic combination of high-gradient magnetic separation, superconducting magnetic separation, and flotation technology, achieving efficient extraction of high mud lithium mica in full grain sizes. This research provides a reference for the efficient development and utilization of complex lithium mica ores.